2022
DOI: 10.3389/fpsyg.2022.800727
|View full text |Cite
|
Sign up to set email alerts
|

Qigong Training Positively Impacts Both Posture and Mood in Breast Cancer Survivors With Persistent Post-surgical Pain: Support for an Embodied Cognition Paradigm

Abstract: Theories of embodied cognition hypothesize interdependencies between psychological well-being and physical posture. The purpose of this study was to assess the feasibility of objectively measuring posture, and to explore the relationship between posture and affect and other patient centered outcomes in breast cancer survivors (BCS) with persistent postsurgical pain (PPSP) over a 12-week course of therapeutic Qigong mind-body training. Twenty-one BCS with PPSP attended group Qigong training. Clinical outcomes w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 103 publications
(132 reference statements)
0
5
0
Order By: Relevance
“…Lastly, men benefited more from the qigong exercises than did the women. Quixadá, et al [17] conducted a study to determine the effect of qigong exercises on the posture and mood of 21 breast cancer survivors who had persistent post-surgical pain.…”
Section: Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, men benefited more from the qigong exercises than did the women. Quixadá, et al [17] conducted a study to determine the effect of qigong exercises on the posture and mood of 21 breast cancer survivors who had persistent post-surgical pain.…”
Section: Cancermentioning
confidence: 99%
“…In the West, it is sometimes used in conjunction with mainstream medicine as a supplementary tool to treat symptoms of various diseases and ailments [1][2][3][4][5][6][7][8][9][10]. Numerous studies have found that qigong can aid in the treatment of arthritis [11], back pain [12], cancer [13][14][15][16][17], cognitive impairment [18,19], Covid-19 [20,21], COPD [22], depression and anxiety [23][24][25][26], fatigue [27], hypertension [28,29], muscle strength and posture [30], Parkinson's disease [31,32], stroke [33], and tertiary-care pain management [34].…”
Section: Introductionmentioning
confidence: 99%
“…Generally, these TCM techniques have been used to partially alleviate the adverse side-effects of western cancer treatments, such as nausea and depression, and have often improved the quality of life, although at least one qigong practitioner claims that the practice of qigong has actually cured her of stage three lymphoma [54]. Qigong and tai chi have been used successfully in the treatment of breast cancer [55][56][57][58][59][60][61][62][63][64], cognitive impairment [65,66], colorectal cancer [67,68], fatigue [69][70][71], gastrointestinal cancer [72], hematological malignancies [73], the immune system [74], pain management [75][76][77], quality of life [78][79][80][81][82][83], sleep disturbance [84], and symptom management [85], usually in conjunction with Western medicine, although some Asian studies have found that tai chi and qigong have been effective when used alone. In fact, some Chinese hospitals are devoted entirely to treatment of cancer and other diseases using tai chi and/ or qigong exclusively.…”
Section: Cancer Studiesmentioning
confidence: 99%
“…There have been five qualitative studies on posture to date, which have predominantly focused on Eastern mind-body practices in clinical practice. Narrative analysis from qualitative interviews found that upright qigong postures (a system of co-ordinated body postures, breath, and meditation) during a 12-week treatment helped breast cancer survivors reconnect their mind and body, lessen their post-surgical pain, and foster acceptance of and confidence in their bodies [17]. Similarly, using semi-standardised interviews, Ref.…”
Section: Introductionmentioning
confidence: 99%